Barrett's esophagus: cancer and molecular biology. (11th October 2013) - Gibson, Michael K.; Dhaliwal, Arashinder S.; Clemons, Nicholas J.; Phillips, Wayne A.; Dvorak, Katerina; Tong, Daniel; Law, Simon; Pirchi, E. Daniel; Räsänen, Jari; Krasna, Mark J.; Parikh, Kaushal; Krishnadath, Kausilia K.; et al.
Abstract : The following paper on the molecular biology of Barrett's esophagus (BE) includes commentaries on signaling pathways central to the development of BE including Hh, NF‐κB, and IL‐6/STAT3; surgical approaches for esophagectomy and classification of lesions by appropriate therapy; the debate over the merits of minimally invasive esophagectomy versus open surgery; outcomes for patients with pharyngolaryngoesophagectomy; the applications of neoadjuvant chemotherapy and chemoradiotherapy; animal models examining the surgical models of BE and esophageal adenocarcinoma; the roles of various morphogens and Cdx2 in BE; and the use of in vitro BE models for chemoprevention studies.